2018
DOI: 10.1017/s1368980018001672
|View full text |Cite
|
Sign up to set email alerts
|

Spanish adaptation and validation of the Child Food Security Survey Module (CFSSM-S)

Abstract: The CFSSM-S is the first validated instrument to assess food insecurity with psychometric guarantees in Spanish adolescents. Researchers and health practitioners in Spain could use this self-reported questionnaire to gain more information about adolescent health in relation to food insecurity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…The most endorsed items were those related to worrying about food at home run out and meals only including cheap foods because the family did not have enough money, which was in agreement with the results from previous studies [12,13,43,44].…”
Section: Discussionsupporting
confidence: 91%
“…The most endorsed items were those related to worrying about food at home run out and meals only including cheap foods because the family did not have enough money, which was in agreement with the results from previous studies [12,13,43,44].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, two studies (Lazaratou et al , 2017; Shankar-Krishnan et al , 2018) examined food insecurity in a sample of adolescents. A study in Greece (Lazaratou et al , 2017) reported that 17.3% of adolescents during the previous month of the study, encountered at least one condition of household food insecurity, while in Spain (Shankar-Krishnan et al , 2018) a study that aimed to validate the Child FSSM in the Spanish population, found that 18.3% of participants were food insecure. Kastorini et al (2016) reported food insecurity in a sample of Greek students at 59.6%, and Zace et al (2019) reported that 15.4% of Italian children, were food insecure.…”
Section: Resultsmentioning
confidence: 99%
“… For simplicity reasons the studies by Shankar-Krishnan et al (2018), Esturk et al (2014), Endeweld et al (2018), Ganhao-Arranhado et al (2018), Laurence et al (2017), Theodoridis et al (2018), Grammatikopoulou et al (2019), Dalma et al (2018), Pilot et al (2014), Baptista et al (2018) and Zamora‐Sarabia et al (2019) are not presented in this table because the sample size is less than 500 participants…”
Section: Figurementioning
confidence: 99%
“…Beyond data on the rate of food insecurity in different groups, several studies have examined risk factors and correlations for food insecurity (for example, [63,65,94,96,97,100,101,[114][115][116]), revealing its association with structural conditions such as poverty, unemployment or low work intensity or employment precarity, housing tenure, low incomes, and low levels of education. The increase in food insecurity risk in households headed by women and those with children is well-documented [117][118][119][120], and new research is emerging on its prevalence among youth [96,116] and older adults [97,121].…”
Section: Correlatesmentioning
confidence: 99%